Sistem Pakar dalam Menganalisis Penyakit Kelenjar Getah Bening Menggunakan Metode Certainty Factor - Sri Layli Fajri; Gunadi Widi Nurcahyo (Rektorat Universitas Putra Indonesia YPTK Padang, 2021)
In general, a person is difficult do dermine whether a lump or swelling of the lymph nodes in the body, is just a normal lump or whether it has become cancer. If the lumph does not go away whitin a few days, the patient is required to immediately consult a doctor to get detailed information about the disease and how to treat it. Lymph nodes scattered in the human body are round and are part of the lymphatic system that plays a role in fighting viruses that enter the body. The cause of these enlarged lymph nodes can be due to the type of food consumed, congenital disease in the patient’s body (comorbid), infection to lymph node cancer (lymphoma). For this reason, an Expert System is needed by applying the Certainty Factor method in order to assist the public in analyzing lymph node disease by answering several questions regarding the symptoms experienced. This system is implementad using the PHP programming language and MySQL database. The result of this study show that the Certainty Factor method can work well in the Expert System analysis process. From the result of system trials with several patient data, the disease accuracy rate in the patient named S is 63% and the disease accuracy rate in the patient named MR is 68%. Besides being useful for an expert, this Expert System can help patients to find out the type of disease they are suffering from, the accuracy of disease, the method of treatment and a guide for making decisions.